Is There A Different Influence of Interactive-Based Methods on Student Social Interaction During E-Learning? - Seviana, Fransisca Laora; Sitompul, Nurmida Chaterine; Degeng, I Nyoman Sudana (Universitas Pendidikan Indonesia, 2021)
There are various kinds of interaction-based E-Learning methods that can be used by educational institutions during the Covid 19 Pandemic, including the Inter-group collaborative and competitive method. This type of research is quantitative comparative using the T test to determine differences in social interactions that occur in students before using collaborative and competitive methods-Inter-group with after using collaborative and competitive-Inter-group methods. The number of samples used in this study were 62 Widya Kartika University students divided into 2 classes, 24 students in the experimental class and 38 students in the control class. The results showed that there were differences in social interaction before and after using the inter-group and collaborative competitive methods. The recommendation of this study is that the interaction-based method can be used as a learning method to increase student social interaction during e-learning.